Developing a closed-loop supply chain model with price and quality dependent demand and learning in production in a stochastic environment. Issue 2 (2nd April 2020) - Giri, B. C.; Masanta, M.
Abstract : In this paper, we develop a closed-loop supply chain model with two suppliers, one manufacturer and one retailer. The manufacturer produces a single product in batches using fresh raw materials and used items. Fresh raw materials can be obtained from primary and secondary suppliers. The primary supplier is cheaper but may not provide the exact ordered quantity, whereas the secondary supplier is expensive but always offers the exact ordered quantity. Random return of used product and stochastic lead time at the retailer are assumed in this model. The market demand of the finished product is linearly dependent on the retail price and quality, and the production process is subject to learning. A numerical example is taken to illustrate the developed model and perform sensitivity analysis. It is observed that learning in production has significant positive effect on the optimal decisions of the closed-loop supply chain.